2016
DOI: 10.1038/srep26687
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired Hybrid Carbon Nanotube Muscles

Abstract: There has been continuous progress in the development for biomedical engineering systems of hybrid muscle generated by combining skeletal muscle and artificial structure. The main factor affecting the actuation performance of hybrid muscle relies on the compatibility between living cells and their muscle scaffolds during cell culture. Here, we developed a hybrid muscle powered by C2C12 skeletal muscle cells based on the functionalized multi-walled carbon nanotubes (MWCNT) sheets coated with poly(3,4-ethylenedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…In order to effectively apply an engineered tissue construct as an in-vitro tissue model, a new analysis system will be important. In this study, contraction displacement was analyzed using a motion analysis tool, similar to previous studies 24 , 25 . This measurement was useful to display the physiological responses of the myofiber sheet construct.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to effectively apply an engineered tissue construct as an in-vitro tissue model, a new analysis system will be important. In this study, contraction displacement was analyzed using a motion analysis tool, similar to previous studies 24 , 25 . This measurement was useful to display the physiological responses of the myofiber sheet construct.…”
Section: Discussionmentioning
confidence: 99%
“…Myofiber sheets were observed microscopically and the EPS-induced muscle contraction was monitored sequentially using a CCD camera (Basler Ace, Basler AG, Germany; 30 frames/s) by phase contrast microscopy. Cell shortening distances were calculated using a motion analysis tool ViewPoint (Glenallan Technology Inc., Clinton, NY, USA) 24 , 25 . Even if the myofiber sheets were produced under the same culture conditions (on Fib/Mtr gel, in neurobasal medium, for 3 weeks), cell conditions (donor, passage number, seeding density etc.)…”
Section: Methodsmentioning
confidence: 99%
“…4C4). The authors demonstrated that the conductive nature of the biohybrid device permitted actuation at a faster rate by reducing the muscle refractory period (65).…”
Section: Actuators Based On Engineered Skeletal Muscle Tissuementioning
confidence: 99%
“…A number of advances have recently been made in creating materials often involving electrospinning, that direct either a partial or complete move away from man/animal tissues for use in muscle-based pathologies [36]. Many of the artificial materials support the differentiation and fusion of muscle stem cells, into ordered myotubes [37]. However, none, to our knowledge, have investigated the movement of SC in these matrixes, nor whether they occur in an amoeboid manner, let alone if their physical properties support myogenic conversion of non-muscle cells.…”
Section: Discussionmentioning
confidence: 99%